2018
DOI: 10.1186/s12885-018-4230-z
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil to lymphocyte ratio in determining the prognosis of head and neck cancer: a meta-analysis

Abstract: BackgroundRecent studies have reported a relationship between prognosis and neutrophil-to-lymphocyte ratio (NLR) in patients with head and neck cancer (HNC). As the results are still controversial, we conducted a meta-analysis of pretreatment NLR in peripheral blood and prognosis in HNC patients.MethodsWe retrieved articles from PubMed, Medline, Cochrane Library, Embase and Web of Science. A comparative analysis was conducted for the effect of pretreatment NLR in peripheral blood on overall survival (OS), prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 54 publications
(52 reference statements)
5
63
0
2
Order By: Relevance
“…The NLR was defined as the absolute neutrophil count divided by the absolute lymphocyte count within 2 weeks before the initial treatment. [4][5][6][7][8][9][10][11][12][13][14] The cutoff value calculated from the ROC curve, mean, tertile, or median in previous studies varied from 1.98-5; 4-11 thus, the standard cutoff value remains unknown. In the current study, the cutoff value was defined as the mean value of the NLR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLR was defined as the absolute neutrophil count divided by the absolute lymphocyte count within 2 weeks before the initial treatment. [4][5][6][7][8][9][10][11][12][13][14] The cutoff value calculated from the ROC curve, mean, tertile, or median in previous studies varied from 1.98-5; 4-11 thus, the standard cutoff value remains unknown. In the current study, the cutoff value was defined as the mean value of the NLR.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The peripheral neutrophil-to-lymphocyte ratio (NLR) is a well-known inflammatory marker. Several authors have previously reported that a high NLR is significantly associated with poor survival in solid cancers, [4][5][6][7][8][9][10][11][12][13][14] including head and neck squamous cell carcinoma and breast cancer. However, whether the NLR affects prognosis in patients with parotid cancer remains unknown; therefore, the current study aimed to clarify this question.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of neutrophil infiltration by tumor cells has been reported to promote tumor growth and progression through remodeling of the extracellular matrix and activation of inflammatory markers, whereas lymphocyte infiltration is thought to be associated with control of cancer progression, especially when T4 helper and T8 suppressor lymphocytes are involved . Not surprisingly, a high NLR has been shown to be a significant predictive factor for survival in patients with cancer, including solid neoplasms such as head and neck cancer …”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] Not surprisingly, a high NLR has been shown to be a significant predictive factor for survival in patients with cancer, including solid neoplasms such as head and neck cancer. 10,16,20,[43][44][45][46] Correlation with survival endpoints in laryngeal cancer patients has been investigated in a small number of studies (Table II), despite their anatomical and pathological specificities. [11][12][13]18,47,48 Karpathiou et al found an association between the NLR and induction chemotherapy in a series of 83 head and neck cancer patients, of whom only 11 had laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11 Yu ve ark.nın yaptığı bir metaanalizde ise yüksek NLR olan baş-boyun kanserli hastalarda lokal invazyon, uzak metastaz eğilimli olduğu ve kötü prognozu gösterdiği bildirilmektedir. 12 Eş zamanlı kemoradyoterapi ile tedavi edilen baş-boyun kanserlerinde, lenfosit/monosit oranının bağımsız bir prognostik faktör olabileceği görüşüne varılmıştır. 13 Çalışmamızda da NLR seviyesi benign lezyonlarda 1,84, malign tümörlerde 2,68 olarak tespit edilmiştir.…”
Section: Bulgularunclassified